The Importance of Patency in Patients with Critical Limb Ischemia Undergoing Endovascular Revascularization for Infrapopliteal Arterial Disease - Baumann, Frederic; Ozdoba, Christoph; Gröchenig, Ernst; Diehm, Nicolas (Frontiers in Cardiovascular Medicine, 2015)
Critical limb ischemia (CLI) represents the most severe form of peripheral arterial disease (PAD) and frequently occurs in medically frail patients. CLI patients frequently exhibit multi-segmental PAD commonly including the tibial arterial segment. Endovascular therapy has been established as first-line revascularization strategy for most CLI patients. Restenosis was reported to occur in up to more than two thirds of CLI patients undergoing angioplasty of complex tibial arterial obstructions. Nevertheless, favourable clinical outcomes were observed for infrapopopliteal angioplasty when compared with bypass surgery despite higher patency rates for the latter. Based on these observations, infrapopliteal patency was considered to be only of secondary importance upon clinical outcomes in CLI patients. In contrast to these earlier observations, however, recent findings from two randomized clinical trials indicate that infrapopliteal patency does impact on clinical outcomes in CLI patients. Purpose of the present manuscript is to provide a critical reappraisal of the present literature on the clinical importance of tibial arterial patency in CLI patients undergoing endovascular revascularization and to discuss utility and limitations of currently available anti-restenosis technologies.